STRATEGI BRUNEI DARUSSALAM DALAM MENGEMBANGKAN INDUSTRI PANGAN HALAL MENGHADAPI PASAR HALAL GLOBAL - Rosalina, Annisa; Saeri, M. (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2020)
This research will analyze how Brunei is trying to diversify its economy through the halal product industry. Brunei’s economy relies on its oil exports and the country planned to diversify its economy. The halal industry is starting to play an important role in the global market. Supported by the availability of natural and human resources as well as the supporting social, cultural and political conditions, Brunei has adopted a strategy to contribute to the global halal market in the halal food industry sector.This qualitative research is document analysis using data from books, journals, newspaper, and websites to describe the issues raised. National-state level analysis with liberalism perspectives about economic diplomacy theory was use to explain the strategies used by Brunei.The result showed that Brunei focus on developing domestic products with a strict certification commitment. Brunei also cooperates with using Brunei Halal branding on products manufactured by companies from other countries. Investment in national companies and the establishment of special industrial areas is also carried out as part of a strategy to deal with the expansion of the halal market which is very important for Brunei’s interest.Keywords: Strategy, Economic Diplomacy, Halal Food Industry, Global Halal Market.